Charles Perrault and the Evolution of “Little Red Riding Hood” - Vaz da Silva, F. (Marvels and Tales, 2016)
I examine the place of Perrault’s “Le Petit Chaperon rouge” within the tradition of “Little Red Riding Hood” (ATU 333). I address the thematic links between Perrault’s conte and the oral texts and consider the “Little Red Riding Hood” theme up to the present day. Overall, I tease out the red thread connecting Perrault’s text with the oral variants of yore and the present-day recreations and make the case that Perrault’s literary touches launched a hitherto obscure oral theme into its present spell of multimedia celebrity.